2016
DOI: 10.1021/jacs.5b12209
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Promiscuity of Ancestral Esterases and Hydroxynitrile Lyases

Abstract: Catalytic promiscuity is a useful, but accidental, enzyme property, so finding catalytically promiscuous enzymes in nature is inefficient. Some ancestral enzymes were branch points in the evolution of new enzymes and are hypothesized to have been promiscuous. To test the hypothesis that ancestral enzymes were more promiscuous than their modern descendants, we reconstructed ancestral enzymes at four branch points in the divergence hydroxynitrile lyases (HNL’s) from esterases ~100 million years ago. Both enzyme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
102
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(108 citation statements)
references
References 92 publications
5
102
0
Order By: Relevance
“…Esterase is predicted to be the ancestor of a number of different types of enzymes (25). In the research of evolutionary analysis, Devamani and his coworkers found that the predicted ancestral enzymes of hydroxyl nitrile lyases shared the Ser-His-Asp catalytic triad and that they had a conserved function of hydrolysis of esters (29). We found that the members of the ␥-lactamase family always have characteristics that are more or less similar to those of the esterase family.…”
Section: Discussionmentioning
confidence: 65%
“…Esterase is predicted to be the ancestor of a number of different types of enzymes (25). In the research of evolutionary analysis, Devamani and his coworkers found that the predicted ancestral enzymes of hydroxyl nitrile lyases shared the Ser-His-Asp catalytic triad and that they had a conserved function of hydrolysis of esters (29). We found that the members of the ␥-lactamase family always have characteristics that are more or less similar to those of the esterase family.…”
Section: Discussionmentioning
confidence: 65%
“…Enzyme catalytic promiscuity is the hidden ability of an enzyme to catalyze more than one type of chemical transformation (1,2). Lipase is one of the most popular biocatalysts in this research area due to its excellent catalytic performance in many kinds of reactions (Aldol reaction, Morita-Baylis-Hillman reaction, Mannich reaction, Henry reaction, Markovnikov addition, Michael addition, Hantzsch reaction, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Several of these ancestors were catalytically promiscuous 8,17 . HNL1 catalyzed mainly hydroxynitrile lyase cleavage, but also showed low remaining esterase activity.…”
Section: Introductionmentioning
confidence: 99%